APPLICATION OF NAIVE BAYES ALGORITHM IN EDUCATIONAL GAMES LEARN TO WRITE AKSARA BALI - Vyasa, I Made Satya; Arta Wibawa, I Gede; Anom Cahyadi Putra, I Gusti Ngurah; Arya Kadyanan, I Gusti Agung Gede; Sanjaya ER, Ngurah Agus; Hendra Suputra, I Putu Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 3 (2023): JELIKU Volume 11 No 3, February 2023DO - 10.24843/JLK.2023.v11.i03.p16, 2022)
Balinese script is a script from the Balinese area that was commonly used by people in ancient times to describe a word, there are many ways to keep this script sustainable and not extinct. One of them is by making a Balinese character recognition game. Which in this application the user will provide input in the form of Balinese characters written on the application, which then the input will go through a preprocessing process and then proceed with diagonal feature extraction, then the results of the feature extraction will go through a classification process using the Naïve Bayes method. The result is a web-based application that can recognize Balinese script writing using the Naïve Bayes classification method with an accuracy rate of 70.3% and get a good response from every respondent who has tested the application. Keyword : Balinese Scription, Diagonal Feature Extraction, Naïve Bayes.